Variations in pulmonary fissural anatomy: a medicolegal autopsy study of 256 cases. Issue 4 (10th November 2019) - Bostanci, Korkut; Ozyurtkan, Mehmet Oguzhan; Polat, Mehmet Oguz; Batirel, Hasan; Lacin, Tunc; Yuksel, Mustafa; Stamenovic, Davor
Abstract: Background: We aimed to document the anatomical variations of pulmonary fissures found during routine forensic autopsies. Methods: A total of 256 pairs of lungs were investigated. Presence of any variant and accessory fissures was noted. Results: Seventy‐seven percent of the lungs had anatomical variations. In about 2/3 of the cases, oblique fissures were incomplete on both sides. The horizontal fissure was incomplete in 68.4%, and absent in 4.3% of the lungs. Twelve left lungs (4.7%) had a horizontal fissure. Accessory fissures were observed in 35 lungs (13.7%). Azygos lobe variations were detected in 1.7% of the lungs. A superior accessory fissure was present in 6.2% and 2% of right and left lungs, respectively. Conclusion: This and previous similar studies demonstrate the existence of several different anatomical fissural variations in the lungs. Clinicians, radiologists and surgeons should keep these in mind to better evaluate and treat their patients. Abstract : We aimed to determine the anatomical fissural variations during routine forensic autopsies. This and previous similar studies demonstrate that there exist several different anatomical fissural variations in the lungs. Clinicians, radiologists and surgeons should kept them in mind to better evaluate and treat their patients.